2004
DOI: 10.1007/s11661-004-0014-y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of prehafnizing on morphological development of a chemical vapor deposition aluminide coating formed on single-crystal Ni-based superalloy

Abstract: We examined a sequential Hf doping procedure, which consisted of (1) "prehafnizing" the surface of a single-crystal Ni-based superalloy (RENÉ N5) with HfCl 4 and H 2 , and (2) aluminizing with AlCl 3 and H 2 , as a means of incorporating Hf as a dopant in the aluminide coating matrix. The prehafnized layer on RENÉ N5 substrate significantly altered the growth behavior and therefore the morphology of the resulting aluminide coating. With the prehafnizing step, the coating layer became much thinner with a signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Furthermore, the recent work of Vande Put et al [68] has shown no significant differences in microstructure between Hf-free beNiPtAl diffusion aluminides and Hf-doped coatings containing w0.2 at.% Hf. It has also been reported that reactive elements could inhibit coating/substrate interdiffusion if they formed discrete barriers to diffusion in the form of stable reactive element-containing phases along the coating/substrate interface [55,56,60]. This has been demonstrated to some extent by the work of Haynes et al [56] who showed that the formation of a Ni 3 Hf-type layer could limit Al depletion during oxidation testing at 1150 C. Given that grain boundaries, like dislocation lines and external surfaces, act as short-circuit pathways for diffusion, it is feasible that elemental diffusion from a coating layer could also be inhibited by the formation of stable precipitates along grain boundaries.…”
Section: Coating/substrate Interdiffusionmentioning
confidence: 99%
“…Furthermore, the recent work of Vande Put et al [68] has shown no significant differences in microstructure between Hf-free beNiPtAl diffusion aluminides and Hf-doped coatings containing w0.2 at.% Hf. It has also been reported that reactive elements could inhibit coating/substrate interdiffusion if they formed discrete barriers to diffusion in the form of stable reactive element-containing phases along the coating/substrate interface [55,56,60]. This has been demonstrated to some extent by the work of Haynes et al [56] who showed that the formation of a Ni 3 Hf-type layer could limit Al depletion during oxidation testing at 1150 C. Given that grain boundaries, like dislocation lines and external surfaces, act as short-circuit pathways for diffusion, it is feasible that elemental diffusion from a coating layer could also be inhibited by the formation of stable precipitates along grain boundaries.…”
Section: Coating/substrate Interdiffusionmentioning
confidence: 99%